THE IMPORTANCE OF MAINTAINING MENTAL HEALTH INPANDEMIC COVID- 19 (PSYCHOEDUCATION - izma daud; izma daud (UMBanjarmasin, 2021)
One of the impacts of the 2019-2020 Coronavirus pandemic is on education around the world, which has led to the closure of large areas of schools, madrasas, universities and Islamic boarding schools. UNESCO (United Nations Educational, Scientific and Cultural Organization) on March 4 2020 suggested the use of distance learning and opened an educational platform that schools and teachers could use to reach learners remotely and limit educational distractions.